The landscape of man : shaping the environment from prehistory to the present day - Jellicoe, Geoffrey; Jellicoe, Susan (London : Thames and Hudson, 1975)
This volume looks at the landscape of 28 cultures, ranging from ancient Mesopotamia to the present day, and shows how the environment is conditioned by the philosophy and religion of each civilization. A selection from Geoffrey Jellicoe's "The Atlanta Historical Garden" is included.
Introduction: landscape and civilization -- PART ONE. From prehistory to the end of the seventeenth century -- PART TWO. The evolution of modern landscape
Includes bibliographical references and index.
Keywords: LANDSCAPE ARCHITECTURE -- HISTORY; NATURE -- EFFECT OF HUMAN BEINGS ON -- HISTORY